Challenges of conflicting school reforms : effects of New American Schools in a high-poverty district - Berends, Mark, 1962- (Rand, 2002)
New American Schools (NAS) offers whole-school designs for schools and districts seeking to significantly raise the achievement of large numbers of students. This work has evaluated NAS reforms' effects on students and teachers in high-poverty schools.
"Supported by New American Schools."
"Rand Education."
"MR-1483-EDU"--Page 4 of cover
Keywords: New American Schools (Organization); School improvement programs -- United States -- Case studies.; School improvement programs -- Texas -- San Antonio.; Educational change -- United States -- Case studies.; Educational change -- Texas -- San Antonio.; Poor children -- Education -- United States -- Case studies.; Poor children -- Education -- Texas -- San Antonio.; Enseignement -- Réforme -- États-Unis -- Études de cas.; Enseignement -- Réforme -- Texas -- San Antonio.; Enfants pauvres -- Éducation -- États-Unis -- Études de cas.; Enfants pauvres -- Éducation -- Texas -- San Antonio.; EDUCATION -- Administration -- General.; EDUCATION -- Educational Policy & Reform -- General.; Educational change; Poor children -- Education; School improvement programs; Texas -- San Antonio; United States; Case studies